Perancangan Aplikasi Mobile Pengenalan Baju Adat Nusantara sebagai Media Pembelajaran Budaya Indonesia - Muhammad Fauzi Firdaus; Theofilus Herly Hatonangan Samosir (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Indonesia has a wide diversity of cultures, one of which is traditional clothing that represents the identity of each region. However, technological developments and the influence of foreign cultures have reduced public interest, especially among younger generations, in local cultural heritage. The lack of engaging learning media is also one of the factors contributing to the low level of public knowledge regarding traditional clothing of the Indonesian archipelago. This study aims to design a mobile-based application for introducing traditional Indonesian clothing as an interactive and easy-to-use cultural learning medium. The research method used in this study is Research and Development (R&D), consisting of needs analysis, system design, application implementation, testing, and evaluation stages. The system design process uses Unified Modeling Language (UML), while the application is developed using the Android platform. The developed application provides features such as regional traditional clothing information, image galleries, data search functions, and educational quizzes to improve user interaction. The results of the study indicate that the designed mobile application can serve as a more effective and engaging cultural learning medium compared to conventional learning methods. Based on Black Box Testing results, all